TIKTOK IN LEARING ENGLISH: EXPLORING 12TH GRADE STUDENTS’ SATISFACTION THROUGH @NOFREEADI10 AND @MR.JOHNHIDAY ACCOUNTS - syifha Asyura; Pipit Novita (JEELL (Journal of English Education, Linguistics and Literature), 2024)
TikTok is one of the media facilities that is quite popular with students, because by using TikTok, students can develop their creativity in creating content such as making videos about writing vocabulary in English. The aim of this research is to find out whether there is a difference in satisfaction in learning English at Budi Luhur High School via social media TikTok, especially with the accounts @nofreeadi10 and @mr.johnhiday. Researchers made differences in satisfaction using the Uses and Gratification theory, this theory was redeveloped by Philp Palmgreen who divided satisfaction into two, namely satisfaction sought (Gratification Sought) and satisfaction obtained (Gratification Obtained). The research methodology used is quantitative with descriptive analysis and the differences with inferential statistic (t-test). The method used is a survey method using a questionnaire as the instrument. The sample used in this research was 100 out of 142 students. Meanwhile, the data analysis technique used is the t-test and mean comparison test. The results of this research showed that the data obtained was sig 0.000 with a sig level of 0.05 (sig 0.000 < 0.05). The results can be concluded, there is a difference in satisfaction via TikTok accounts @nofreeadi10 and @mr.johnhiday in learning English.